PSB33 sustains photosystem II D1 protein under fluctuating light conditions - Rikard Fristedt; Andrea Trotta; Marjaana Suorsa; Anders K Nilsson; Roberta Croce; Eva-Mari Aro; Björn Lundin (OXFORD UNIV PRESS, 2022)
On Earth, solar irradiance varies as the sun rises and sets over the horizon, and sunlight is thus in constant fluctuation, following a slow dark–low–high–low–dark curve. Optimal plant growth and development are dependent on the capacity of plants to acclimate and regulate photosynthesis in response to these changes of light. Little is known of regulative processes for photosynthesis during nocturnal events. The nucleus-encoded plant lineage-specific protein PSB33 has been described as stabilizing the photosystem II complex, especially under light stress conditions, and plants lacking PSB33 have a dysfunctional state transition. To clarify the localization and function of this protein, we used phenomic, biochemical and proteomics approaches in the model plant Arabidopsis. We report that PSB33 is predominantly located in non-appressed thylakoid regions and dynamically associates with a thylakoid protein complex in a light-dependent manner. Moreover, plants lacking PSB33 show an accelerated D1 protein degradation in nocturnal periods, and show severely stunted growth when challenged with fluctuating light. We further show that the function of PSB33 precedes the STN7 kinase to regulate or balance the excitation energy of photosystems I and II in fluctuating light conditions.